How did wars dampen trade in the MENA region? - Karam, Fida; Zaki, Chahir (International Food Policy Research Institute, 2015)
This paper investigates the effects of war on trade in the Middle East and North Africa region (MENA), an area at considerable risk for conflicts. Using an augmented gravity model, we introduce a war variable and distinguish between different types of conflicts. We run a battery of sensitivity analysis tests to control for the endogeneity problem that may arise in our estimation. The results show that, in general, wars have a significantly negative impact on trade (exports and imports); civil conflicts in particular hinder exports, imports, and overall trade significantly. The disaggregated version of the gravity model shows that non-state conflicts have a detrimental effect on bilateral trade flows in manufacturing; however, none of the conflicts modeled affect trade in services. Finally, the outcome of the gravity model for manufacturing has been used to compute ad-valorem equivalents (AVEs) of wars at the country level. We found that, on average, a conflict is equivalent to a tariff of 5 percent of the value of trade. More heterogeneity is observed at the sectoral level, where AVEs range from 4 to 65 percent.